Pityriasis rosea: a distinct entity or viral exanthem? - Dąbrowska, Natalia; Węgrzyn, Piotr; Węgrzyn, Konstancja; Laskowski, Gustaw; Salińska, Anna; Wasilewski, Marcin; Skwara, Julia; Góra, Agnieszka; Nowicki, Maciej; Barański, Dawid (Dermatology Review/Przegląd Dermatologiczny, 2024)
Pityriasis rosea is a well-known, common skin dermatosis in clinical practice. It has a benign self-limiting character and most often does not require any treatment. It is probably caused by reactivation of the human herpes virus-6 and -7. Usually, it occurs in children and young adults and presents a typical course with numerous scaly plaques on the trunk and extremities preceded by the onset of a herald patch. The diagnosis is based on clinical symptoms, however in some of the cases, dermatoscopy, histopathology or other examinations may be helpful to establish the correct diagnosis. Although the disease is typically not dangerous, it can be a therapeutic challenge, especially when its course is atypical or when it occurs during pregnancy and may pose a risk to the fetus. The literature on pityriasis rosea was analyzed to check whether new insights regarding its etiopathogenesis have appeared, or treatment approach has been changed.